Electrochemistry and Spectroelectrochemistry of Luminescent Europium Complexes. Issue 9 (4th May 2016) - Lines, Amanda M.; Wang, Zheming; Clark, Sue B.; Bryan, Samuel A.
Abstract: Fast, cost effective, and robust means of detecting and quantifying lanthanides are needed to support more efficient tracking within the nuclear, medicinal, and industrial fields. Furthermore, methods for isolating lanthanide signal from spectroscopic interferents are also needed. Applying spectroelectrochemistry to the detection of these species can meet those needs. However, application of this technique is limited by the low molar absorptivities and quantum yields of the lanthanides. These limitations can be circumvented by complexing the lanthanides with sensitizing ligands that enhance fluorescence, thereby dropping the limits of detection. Complexation will also cause changes in the electrochemical behavior of the lanthanides. To demonstrate this concept, studies were completed using europium as a model lanthanide in complexes with four different sensitizing ligands, which included 2, 2′‐bipyridine and related derivatives. Results indicate that all four studied complexes demonstrate quasi‐reversible redox couples and improvements in limits of detection where electrochemical and spectroscopic characteristics showed some dependence on attached ligand. All four complexes studied display the necessary characteristics for spectroelectrochemical analysis, which was successfully and reproducibly applied to all Eu complexes. Abstract :